Alpha-Lipoic Acid Protects Cardiomyocytes against Heat Stroke-Induced Apoptosis and Inflammatory Responses Associated with the Induction of Hsp70 and Activation of Autophagy - Hsin-Hsueh Shen; Yu-Shiuan Tseng; Ni-Chun Kuo; Ching-Wen Kung; Sherif Amin; Kwok-Keung Lam; Yen-Mei Lee (Hindawi Limited, 2019)
Heat stroke (HS) is a life-threatening illness and defined as when body temperature elevates above 40°C accompanied by the systemic inflammatory response syndrome that results in multiple organ dysfunctions. α-Lipoic acid (ALA) acts as a cofactor of mitochondrial enzymes and exerts anti-inflammatory and antioxidant properties in a variety of diseases. This study investigates the beneficial effects of ALA on myocardial injury and organ damage caused by experimental HS and further explores its underlying mechanism. Male Wistar rats were exposed to 42°C until their rectal core temperature reached 42.9°C and ALA was pretreared 40 or 80 mg/kg (i.v.) 1.5 h prior to heat exposure. Results showed that HS-induced lethality and hypothermia were significantly alleviated by ALA treatment that also improved plasma levels of CRE, LDH, and CPK and myocardial injury biomarkers myoglobin and troponin. In addition, ALA reduced cardiac superoxide anion formation and protein expression of cleaved caspase 3 caused by HS. Proinflammatory cytokine TNF-α and NF-κB pathways were significantly reduced by ALA treatment which may be associated with the upregulation of Hsp70. ALA significantly increased the Atg5-12 complex and LC3B II/LC3B I ratio, whereas the p62 and p-mTOR expression was attenuated in HS rats, indicating the activation of autophagy by ALA. In conclusion, ALA ameliorated the deleterious effects of HS by exerting antioxidative and anti-inflammatory capacities. Induction of Hsp70 and activation of autophagy contribute to the protective effects of ALA in HS-induced myocardial injury.